ANALYSIS THE IMPLEMENTATION OF SELF DIRECTED LEARNING IN LEARNING ENGLISH FOR SPECIFIC PURPOSE - Gabriel Fredi Daar; Fransiskus Jemadi (STKIP Persada Khatulistiwa Sintang, 2020)
Self Directed Learning is the actions taken by which the students independently take initiative to assess their own learning needs, set up learning goals with implementation of appropriate strategies and evaluate learning outcome. This study aims to find out how Students of Nursing at Unika Santu paulus Ruteng, Flores implement self Directed Learning in learning English for Specific Purposes (ESP). It’s mixed method research combining the use of quantitative and qualitative study. For the purpose of quantitative study, it’s used total sampling. Therefore, all 6th semester students numbered 32 were chosen as the samples of the research. Meanwhile for the purpose of qualitative study, it’s chosen 6 students taken purposively. The research result showed that most students of Nursing Unika Santu Paulus Ruteng 23 (71.9%) implemented medium Self Directed Learning in learning English for Specific Purpose (ESP). It’s furthermore supported by the findings of qualitative study which was elaborated and described based on Self Directed Learning processes namely 1) self learning awareness, 2) planning to learn, 3) learning goal, 4) being discipline to learn, 5) self confident, 6) hard working to learn, and 7) originality. The findings would be the suggestions for school authorities in particular English teacher to plan for applying Self Directed Learning in learning English for Specific Purpose at Nursing Study program Unika Santu Paulus Ruteng, Flores. By knowing earlier the concept and how to apply SDL, students of Nursing have a free will to implement it in learning English.Keywords: SDL, learning English, ESP, nursing students